Risk Analysis of Microfinance Conversion Based on ISO 31000 PT. Bank BRI Syariah. Tbk Aceh - Norlita, Wa Ode; Rarasati, Ayomi Dita (RSF Conference Series: Business, Management and Social Sciences, 2021)
Aceh government issued Aceh Qanun No. 11 of 2018 about Sharia Financial Institutions, which demands that all financial contracts in Aceh adhere to Sharia principles. This regulation has an impact on the Aceh region’s financial business. PT Bank BRI Tbk Aceh has decided to conversion entire financing and funding portfolio to one of its sharia-compliant subsidiaries, PT Bank BRIsyariah Tbk. microfinance portfolio is bigger than other segments. By constructing a risk analysis based on ISO 31000, this study assesses the business risk associated with converting PT Bank BRIsyariah Tbk’s microfinance segment in the Aceh region. The results indicate that twenty risks have been identified and evaluated. Risk can be classified into five broad categories: operational, reputational, strategic, credit, and compliance. The risk analysis results indicate that the risk is significant and requires immediate attention. Operational risk is associated with differences in data capacity, servers, the core banking system, and financing applications, whereas strategic risk is associated with differences in financial analysis, guarantee provisions, and regulations.